The Use Of Social Media And Product Innovation On The Development Of Micro Enterprises In The Trade Sector In Luwu Regency - Lusaima, Andi Lusaima; Haedar Akib; Muh. Rizal S; Henni Zainal (Fakultas Ilmu Sosial dan Hukum, 2024)
The use of social media and product innovation on the development of micro enterprises in the trade sector in Luwu Regency. Thesis. Business Administration Study Program. Department of Administrative Sciences. Faculty of Social Sciences and Law. Makassar public university. (supervised by Haedar Akib and Aris Baharuddin).This study aims to determine the description and influence of the use of social media and product innovation either partially or simultaneously on the development of micro-enterprises in the trade sector in Luwu Regency. The population of this research is the micro business actors in the trading sector in Luwu Regency. Determination The sample used is the sample formulated by Slovin with an error rate of ten percent, the number of samples obtained is as many as one hundred respondents, with data collection techniques namely questionnaires that are tested for validity and reliability. The data obtained were processed using data analysis and the help of SPSS version twenty five which consisted of classical assumption test, multiple linear regression analysis, t test, F test and determinant coefficient. The results showed that the use of social media in the very good category, product innovation in the good category, and business development in the very good category. The results of the reference analysis show that there is a significant influence between the use of social media and product innovation on the development of micro enterprises in the trade sector in Luwu Regency.